HUBUNGAN ANTARA SELF-EFFICACY DENGAN PROKRASTINASI AKADEMIK DALAM PENYUSUNAN PROPOSAL SKRIPSI PADA MAHASISWA KEPERAWATAN SEMESTER AKHIR DI STIKES ESTU UTOMO BOYOLALI - Syamsul Bahri, Ahmad; Arifah, Tsania Azhar; Herbasuki, Herbasuki; Sajidalloh, Farhan Nafis (Jurnal Cakrawala Keperawatan, 2025)
Background: : Preparation of a thesis proposal is an important stage in completing student studies, but is often faced with academic procrastination behavior. One factor that is thought to affect academic procrastination is self-efficacy or individual confidence in completing academic tasks. Objectives: This study aims to determine the effect of health education using sound slide media on knowledge and action in choosing snacks among elementary school age children at SDN Garangan. Objective: This study aims to determine the relationship between self-efficacy and academic procrastination in preparing thesis proposals in final semester nursing students at STIKes Estu Utomo Boyolali. Method: This research is a descriptive study in the form of a correlation study with a cross sectional approach. This research was conducted in March 2025. The sampling technique in this study used total sampling with a total of 49 student respondents. The research instrument used the College Academic Self-Efficacy Scale (CASES) questionnaire to measure self-efficacy and the Academic Procrastination Scale (APS) to measure academic procrastination. Data analysis using Spearman Rank test. Results: The results of the Spearman Rank test showed a p value of 0.000 which means there is a significant relationship between self-efficacy and academic procrastination. The correlation coefficient value shows 0.524 so that between self-efficacy and academic procrastination has a relationship with moderate strength and negative direction. Conclusion: There is a relationship between self-efficacy and academic procrastination in preparing proposals for final semester nursing students at STIKES Estu Utomo Boyolali